Macroalgal Diseases: Exploring Biology, Pathogenesis, and Management Strategies - Damiano Spagnuolo; Giuseppa Genovese (Phycology)
The global seaweed market is expected to reach USD 17.8 billion by 2032, fuelled by growing demand for sustainable and healthy food solutions and expanding applications in agriculture and aquaculture. However, this rapid growth poses significant challenges, particularly in managing diseases that often establish themselves in intensive macroalgal culture facilities. Red rot disease, Olpidiopsis, and green spot disease often affect marine macroalgae species of high commercial interest, as seen in Pyropia/Porphyra as has already happened for “ice-ice” malaise on Kappaphycus, causing huge economic losses. These diseases are caused by infectious agents that find their place in extreme environmental conditions, such as those characterized by sudden changes in temperature and pollution. Despite technological advances aimed at monitoring the well-being of cultivated seaweed, discrepancies between regions’ technological capabilities and species vulnerability exacerbate management difficulties. This review provides an overview of diseases prevalent among marine algae, their impact on aquaculture, and the effectiveness of currently adopted treatments. This study highlights the need to improve disease management strategies and highlights the importance of understanding host–pathogen interactions in order to mitigate future epidemics.